Development and characterization of coconut oil-based phase change material integrated flexible polyurethane biocomposites for thermal energy storage applications - Ustaoglu, Abid; Menbari, Saman; Gencel, Osman; Aydogmus, Ercan; Sari, Ahmet; Yesilata, Buelent; Uzun, Orhan (Elsevier, 2025)
With growing global energy demand and the urgent need to reduce carbon emissions, developing sustainable materials with thermal energy storage capabilities has become essential. This study introduces, for the first time, a flexible polyurethane biocomposite (FPB) containing directly integrated unencapsulated coconut oil-based phase change material (CO-PCM), without micro-shells or encapsulation. This novel approach simplifies fabrication, reduces cost, and enhances thermal and mechanical performance through direct polymer-phase change material interaction. Flexible polyurethane biocomposites incorporating varying concentrations (0 %, 15 %, 30 %, and 45 %) of CO-PCM were synthesized using a two-step method involving polyether polyol, isocyanate, and a catalyst. Increasing CO-PCM content improved the physical and thermal properties of the composites. At 45 wt% CO-PCM, bulk-density increased by 51 %, Shore A hardness by over 43 %, and tensile strength by 14 %, while strain decreased from 82 % to 53 %. Thermal conductivity improved by 15 %, and activation energy rose by 30 %, indicating enhanced thermal stability. The composites were characterized using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), and scanning electron microscopy (SEM). Thermoregulation tests showed that the FPB with 45 % CO-PCM reduced peak surface temperatures by up to 6.8 degrees C during the day and retained 2.4 degrees C more heat at night, contributing to stable indoor thermal conditions. Energy simulations across four climate zones revealed that FPB-45 could reduce heating energy demand by up to 26 % compared to conventional expanded polystyrene (EPS) insulation. CO2 emission analysis indicated up to 10 kg/m2 annual reduction, and up to $1.80/m2 annual savings when using fuel oil, proving its technical and economic viability.
Keywords: Coconut oil; Phase change material; Flexible polyurethane biocomposite; Energy storage properties; Energy and energy efficiency; Renewable energy